HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU SISWI DALAM UPAYA PENGENDALIAN INFEKSI MENULAR SEKSUAL DI SMA IT ABU BAKAR YOGYAKARTA TAHUN 2014 - Margiyati Margiyati; Marmi Marmi (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2015)
ABSTRACT Background: It is estimated that more than 340 million new cases of sexually transmitted infections (STIs) that can be cured (syphilis, gonorrhea, chlamydia, and trichomonas infections) occur each year in men and women aged 15-49 years. The absence of specific subjects that are taught and provide information for high school students, especially girls, became one of the causes of the high incidence of STIs among adolescents .This study aims to determine the relationship between the level of knowledge and attitudes toward student behavior in an effort to control sexually transmitted infections in Abu Bakar  high school (SMAIT Abu Bakar) Yogyakarta.  Methods: This study used a cross sectional descriptive correlation. The sampling technique used is total sampling. The data was collected using a questionnaire, with a sample of 29 students. Analyzed using univariate, bivariate use momment product person, and multivariate use the f-test (ANOVA). Results: The statistical results of this study indicate that as many as five students ( 17.2 % ) had good knowledge level, 19 students ( 57.6 % ) had a pretty good level of knowledge, and as many as five students ( 17.2 % ) had a level of knowledge poorly- STI control efforts. There are 10 students ( 34.5 % ) had a good attitude, 19 students ( 65.5 % ) had a pretty good attitude, and none of the students was ( 0 % ) who have a bad attitude in STI control efforts. While the behavior of students in an effort to control the IMS 100 % better. Bivariate analysis on the relationship with the knowledge level of behavior is p < 0.005 ( 0.536 ) and the relationship with behavioral attitude is p < 0.005 ( 0.088 ). Multivariate analysis between knowledge and attitudes with student behavior in STI control efforts is the F count > F table ( 2,672 > 3,707 ) and significance values in the table = 0.088  where the sig < 0.005.Conclusion: There is no relationship between the level of knowledge and attitudes with student behavior in STI control efforts in Abu Bakar high school (SMA IT) Yogyakarta 2014.